Discrete Pneumatic‐Tendon‐Coupled Actuators with Interconnected Air Circuit for Untethered Soft Robots - Jiutian Xia; Jie Huang; Shiling Fu; Jingting Qu; Liyan Mo; Yunquan Li; Tao Ren; Yang Yang; Yujia Li; Hao Liu (Advanced Intelligent Systems)
Untethered soft robots (USRs) based on single‐actuation methods face inherent limitations due to restricted energy resources, which adversely affect their performance. Pneumatic‐tendon‐coupled actuators (PTCAs) offer an effective approach for USRs by combining the compliance and variable stiffness of pneumatic actuation with the precision and rapid motion control of tendon‐driven actuation. However, current PTCA‐based USRs are limited in versatility and efficiency when executing complex tasks. This research introduces discrete pneumatic‐tendon‐coupled actuators with interconnected air circuit (DPTCAs‐IAC) to address these limitations through two major design approaches: 1) multiple discrete DPTCAs with integrated micro pump, providing additional degrees of freedom and independent motion control while regulating internal pressure without significantly adding weight; and 2) interconnecting multiple DPTCAs through air circuits to facilitate gas flow and enhance efficiency. Theoretical modeling and experimental tests conducted on single DPTCA and DPTCAs‐IAC show that the IAC effectively reduces actuation torque and that opposite‐direction movements consume less energy compared to same‐direction movements. An untethered soft robotic gripper and an untethered quadruped robot with soft legs based on DPTCAs‐IAC are developed. Both demonstrate excellent controllability, compact system integration, and multifunctionality, highlighting the potential of DPTCAs‐IAC in advancing the development of complex untethered soft robots.